The Gingerbread man - Ladybird (London Penguin Books Ltd, 2010)
This Ladybird retelling of The Gingerbread Man is a wonderful introduction to classic fairy tales for toddlers and preschool children. Enjoy reading the simple text together, looking at the bright pictures and feeling the different touch-and-feels on every page
English stories
2 8
Keywords: English stories